Alleged Violation of Article 17 of Law Number 5 of 1999 Regarding Transportation Management Services for Shipping (Export) of Clear Lobster Seeds, Decision Number 04/KPPU-I/2021 Decision Date 09 June 2022 - Alfie, Dhea; Permana, Diki; Santoso, Edi (Formosa Journal of Sustainable Research, 2024)
This study examines the alleged violation of Article 17 of Law Number 5 of 1999 related to the transportation management services for the delivery (export) of clear lobster seeds, based on the Decision of the Business Competition Supervisory Commission (KPPU) Number 04/KPPU-I/2021 dated June 9, 2022. In this case, there are strong indications that several business actors have carried out unhealthy market control practices, which have a negative impact on business competition in the transportation management sector for clear lobster seeds in Indonesia. This study analyzes the impact of the alleged violations on business actors, service quality, innovation, and the development of the national fisheries sector. The conclusions drawn emphasize the importance of law enforcement and regulatory reform to maintain healthy competition in this sector. Recommendations provided include stricter law enforcement, regulatory reform, increased innovation, and protection for small business actors and fishermen affected